TRANSFORMASI PENDIDIKAN AGAMA KRISTEN DI ERA DIGITAL: MEMBANGUN IMAN, KARAKTER, DAN LITERASI SPIRITUALITAS PESERTA DIDIK DALAM ARUS PERUBAHAN ZAMAN (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The development of digital technology has brought significant changes to the world of education, including Christian Religious Education. This change demands a paradigm shift in religious education to ensure its relevance to the context of today's students. This article aims to conceptually examine the transformation of Christian Religious Education in the digital era, focusing on faith development, Christian character formation, and strengthening students' spiritual literacy. This research uses a qualitative approach with a literature review method, namely by reviewing books, journal articles, and scientific literature relevant to the topic of Christian Religious Education and digital development. The results of the study indicate that the digital era presents serious challenges in the form of value relativism, instant culture, and minimal spiritual reflection, but also opens up new opportunities for the development of contextual and transformative faith education. Christian Religious Education plays a strategic role in guiding students to build reflective faith, character rooted in Christian values, and spiritual literacy that helps them make sense of life amidst changing times. With a pedagogical approach that is dialogical, reflective, and adaptive to technology.